2013
DOI: 10.1136/jclinpath-2013-201631
|View full text |Cite
|
Sign up to set email alerts
|

Columnar cell-like changes in the male breast

Abstract: In the male breast, there is an entity sharing morphological features and immunohistochemical profile of columnar cell lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…This might indicate that these clonally negative ducts are of importance in carcinogenesis. These putative precursors seem to be in line with the ‘columnar cell‐like changes’ reported recently by Ni et al . in the male breast.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This might indicate that these clonally negative ducts are of importance in carcinogenesis. These putative precursors seem to be in line with the ‘columnar cell‐like changes’ reported recently by Ni et al . in the male breast.…”
Section: Discussionsupporting
confidence: 90%
“…This might indicate that these clonally negative ducts are of importance in carcinogenesis. These putative precursors seem to be in line with the 'columnar cell-like changes' reported recently by Ni et al 37 in the male breast. In 39 cases within 71 resections (with only six invasive carcinomas), they found distended ducts with a round or undulated outline, and an inner layer of columnar luminal cells that were also CK5/ 6-negative.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They noted columnar cell like changes in 39 patients. The incidence of CCL was similar in malignant and benign lesions [11]. Another recent study found no CCL around invasive cancer, gynaecomastia and normal breast tissue [12].…”
Section: Discussionmentioning
confidence: 90%
“…Of interest as a potential interpretative pitfall, in some cases we found the presence of columnar cell‐like changes, as described by Ni et al ., to also be CK5/6‐negative and diffusely ER‐positive. Although the debate as to whether columnar cell lesions truly exist in the male breast is ongoing, our experience shows that there are ductal changes that occur in the male breast that at least mimic the cytological and immunohistochemical features of columnar cell lesions in females . Their mention here is to indicate the possibility of misinterpreting them as ADH or DCIS by placing too much emphasis on the immunohistochemical staining pattern.…”
Section: Discussionmentioning
confidence: 93%